(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Bladder diverticula are uncommon in clinical practice, with men having a significantly higher prevalence compared to women. This condition is linked to prostate gland disorders that lead to urinary obstruction. While there are no exact figures on its occurrence, treatments typically involve surgery only if complications like residual urine, stones, or tumors arise. Traditional surgical methods for bladder diverticula removal, such as bladder resection or diverticulum neck plastic surgery, are often considered invasive and lengthy, limiting their use in patients with serious health conditions. However, advancements in medical technology have paved the way for minimally invasive transurethral endoscopic procedures as effective alternatives. These procedures are now commonly used for treating lower urinary tract conditions, even in elderly patients with significant comorbidities. Transurethral resection for prostate gland enlargement, in particular, is widely considered the optimal surgical approach for managing bladder diverticula in contemporary practice.Advancements in medical technology have revolutionized the treatment landscape for bladder diverticula. While traditional open surgical interventions were once the primary methods used, the introduction of minimally invasive transurethral endoscopic procedures has significantly improved outcomes and patient recovery times. These modern techniques offer high efficacy, minimal invasiveness, and a reduced risk of complications, making them an attractive option even for older patients with complex health conditions.